Synthesis of Paclitaxel Loaded on Nanoparticles of Archaeosomes and Investigation of Its Anti-cancer Properties - Mazloumi Tabrizi, Maral; Jafarzadeh Rastin, Sepideh; Kabiri, Nahid; Akbarzadeh Khiyavi, Azim (Asian Pacific Journal of Cancer Biology, 2017)
Objective: In this study, the effect of archaeosomal paclitaxel drug on breast cancer MDA-MB231 cell lines was evaluated. Material and method: The experiments were conducted to assess the cytotoxicity of paclitaxel in free form and compare it with archaeosomal form of the drug in vitro. To check the size of archaeosomes, Zetasizer device (DLS) was used. The average size of archaeosom nanoparticles containing paclitaxel drugs 430 nm and surface charge -15 and the average size of control archaeosom nanoparticles without drug 460 nm and surface charge -14 were reported. The effect of archaeosomal drug containing paclitaxel and free drug were examined by MTT test. Results: In both formulations, zeta potential was negative. Nano-archaeosom containing paclitaxel drug had higher physical stability compared with control nano-Archaeosom. Tests showed the killing effect of nano-archaeosome containing paclitaxel formulation tumor cells was more than free formulation. In the other word, nano-archaeosome containing paclitaxel is more effective than free paclitaxel. Conclusion: The experiments showed that the killing effect of tumor cells of nano-archaeosomes formulations containing paclitaxel was more than free formulation. That is, nano-archaeosomes containing paclitaxel was more effective than free form paclitaxel.